Mining Experts in Technical Online Forums - Das Neves, Fernando (2010)
Many organizations use or host discussion lists, in the form of online forums and email lists. Analyzing the content of those discussion lists is an effective solution to the task of expert finding, since experts tend to participate often by giving advice, and receive the best feedback. We present a novel method to identify positive comments that helps to identify experts by combining author statistics with polarity mining. Our method is able to distinguish experts from flamers and other people that simply participates frequently in discussions. We demonstrate the validity of our approach by evaluating it with an online discussion forum in Spanish.